1999
DOI: 10.1007/bf02557241
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the light-front QCD Hamiltonian

Abstract: We propose the light-front Lagrangian and the corresponding Hamiltonian that produce a theory perturbatively equivalent to the conventional QCD in the Lorentz coordinates after the regularization is removed. The regularization used is nonstandard and breaks the gauge invariance. But after the regularization is removed, this invariance is restored by the introduction of a finite number of counterterms with coefficients dependent on the regularization parameters.In this corrected version the counterterms are giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 25 publications
2
79
0
Order By: Relevance
“…We consider this problem for (2+1)-dimensional Yang-Mills theory quantized on the LF where the above mentioned regularization |p − | ε > 0 is applied. Unlike the early considered case of (3+1)-dimensional QCD [12], for (2+1)-dimensional model we can construct renormalized LF Hamiltonian containing no new unknown renormalization parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider this problem for (2+1)-dimensional Yang-Mills theory quantized on the LF where the above mentioned regularization |p − | ε > 0 is applied. Unlike the early considered case of (3+1)-dimensional QCD [12], for (2+1)-dimensional model we can construct renormalized LF Hamiltonian containing no new unknown renormalization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that one can overcome this difficulty by addition of new (in particular, nonlocal) terms to the canonical LF Hamiltonian [12,15,16]. In the case of gauge field theory the infinite number of such terms appears [4,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general nonperturbative renormalization procedure for QCD has recently been outlined by Paston et al [14]. An alternative is to the use of broken supersymmetry as an ultraviolet regulator [15].…”
Section: Introductionmentioning
confidence: 99%
“…These methods will continue to be explored in various contexts, leading eventually to consideration of (supersymmetric) QCD. In fact, Paston et al [17] have already obtained a PV-like regularization of QCD that could, in principle, be solved by DLCQ; however, with present computing power the number of fields is probably too large for meaningful calculations.…”
Section: Future Workmentioning
confidence: 99%